Survey on Asteraceae weeds at Bangladesh Agricultural University campus and reviewed their ethno-botanical uses (Journal of the Bangladesh Agricultural University, 2020)
The cosmopolitan family Asteraceae is the largest family of flowering plants. As a part of taxonomic investigation on the “Weed flora of Bangladesh Agricultural University Campus”, the Asteraceae weed diversity was studied and their ethno-botanical, ethno-medicinal and other uses, and importance were reviewed from published literature. A total of 26 species belongs to 21 genera of this family was collected and identified. In context to the number of species, Blumea was the most dominant genus (with 4 species) followed by Gnaphalium (with 3 species); while 19 genera were represented by single species each at this campus. Among the species, Ageratum conyzoides, Blumea lacera, Mikania cordata, Spilanthes calva, Vernonia cinerea, Xanthium indicum and Youngia japonica were the most population rich and found mostly in the fallow lands, roadsides and levees of crop field. The knowledge of flowering time/period could be helpful for the effective management of the particular weed species. Some of these weed species have ethno-botanical uses e.g., high medicinal value, consumed as vegetable and salad, feed, fodder, etc. The rigorous taxonomic studies would be helpful for the sustainable management of Asteraceae weed species at this campus as well as the country as a whole, which will ensure higher economic returns without disturbing the agro-ecosystems.J Bangladesh Agril Univ 18(1): 17–24, 2020https://doi.org/10.5455/JBAU.94728